2021
DOI: 10.1080/17565529.2021.1930987
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and hunter-gatherers in montane eastern DR Congo

Abstract: Research Highlights• Twa and Tembo perceived reduced rainfall and fog, but increased temperatures• Meteorological data available shows reduced rainfall and increased temperatures• Twa and Tembo reported reduced crop yields and reduced abundance of forest products • Tembo are already implementing some climate adaptation, but not the Twa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 54 publications
6
10
0
Order By: Relevance
“…In the same vein, Lawrence and Vandercar (2015) warned of the consequences of continuing deforestation trends on agricultural productivity in the tropics, because of the induced increase in mean temperature and rainfall disruptions. In our study area, Batumike et al (2021) have shown that local people have been aware of reduced rainfall and fog, and increased temperatures, resulting in reduced crop yields and the rarity of some forest products such as caterpillars, mushrooms and honey. This concurs with the findings of Mubalama et al (2020) who reported that, apart from recognizing increased temperatures and reduced rainfall, local people were progressively devising new strategies (early planting, improved varieties and crop rotation, etc.)…”
Section: Discussionmentioning
confidence: 92%
“…In the same vein, Lawrence and Vandercar (2015) warned of the consequences of continuing deforestation trends on agricultural productivity in the tropics, because of the induced increase in mean temperature and rainfall disruptions. In our study area, Batumike et al (2021) have shown that local people have been aware of reduced rainfall and fog, and increased temperatures, resulting in reduced crop yields and the rarity of some forest products such as caterpillars, mushrooms and honey. This concurs with the findings of Mubalama et al (2020) who reported that, apart from recognizing increased temperatures and reduced rainfall, local people were progressively devising new strategies (early planting, improved varieties and crop rotation, etc.)…”
Section: Discussionmentioning
confidence: 92%
“…For example, farmers, hunters, and fishers have experiential knowledge of local ecology that is valuable for environmental and conservation research (e.g. Batumike et al 2022).…”
Section: How Can Public Trust Be Improved?mentioning
confidence: 99%
“…Research on local knowledge can also help us to understand smallholder farmers concerns and priorities, offering new opportunities to better target climate change adaptation policies and development interventions that are more fitted to the local context(s) [1,3]. Smallholder farmers have addressed (or tried to address) the effects of climate change, including food shortages and reduced health and income, e.g., [4]. by implementing different measures, often classified as 'coping strategies'-when addressing the post-disaster damages-or as 'adaptation of strategies', when they are carried out before a hazardous climate event occurs [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work from Mt. Kahuzi in eastern DR Congo, which also combined gauge-based rainfall estimates with farmers' perceptions, showed changing season lengths but reduced overall rainfall [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation